Pengaruh Konseling Modification Mindful Self Compassion (MMSC) Terhadap Self Compassion Siswa Madrasah Aliyah - Haryani, Ninik; Hambali, IM; Setiyowati, Arbin Janu (Buletin Konseling Inovatif, 2025)
Low self-compassion of students will affect the completion of their developmental tasks and have a negative impact on aspects of their lives. This has become an urgency for research to be carried out which aims to determine the effectiveness of Modification Mindful Self-Compassion (MMSC) group counseling to increase the self-compassion of MA students. This research method is a quasi-experiment with a nonequivalent control group design that has an experimental group and a control group. The research subjects were 5 students who were determined through non-probability sampling techniques with purposive sampling with certain criteria specifically students who were class X at MAN 4 Kampar with low self-compassion scale results. The research procedures are pre-group counseling, intervention, and post-group counseling. Data were collected using a questionnaire with a self-compassion scale which was conducted as a pretest before the intervention and a posttest after the intervention. After the data is obtained, the data is then processed using data analysis techniques is descriptive data analysis and the Wilcoxon test. The research results show that Modification Mindful Self Compassion (MMSC) Group Counseling is effective in increasing the self compassion of MA students.